Strategi Pengembangan Taman Rekreasi Kalianget Kabupaten Wonosobo - Nurcahyanto, Herbasuki; Subowo, Ari; Hani’in, Septiati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Kalianget Tourismt Park, is one of tourism destination in Kabupaten Wonosobo, that having lots of potential to be developed. But, the condition is not comparable yet, with the potencies. The questions are: what internal and external factors, and how regional Government Kabupaten Wonosobo to develop the potencies of Kalianget Tourism Park. This research aims to identify internal and external factors and analyze how Regional Government Kabupaten Wonosobo, to develop the potencies of Kalianget Tourism Park. Using theory of strategic management, this research using SWOT Analysis to identify the strengths, weaknesses, opportunities, and threats, in strategic environment. This research is a qualitative descriptive type of research. Strategic management is important to do, and needed by department to plan the program. The result shows that there are eight issues, in the process to developing Kalianget Tourism Park. After using Litmus test measurement to evaluate the strategic issues, the two most strategic issues can be found. They are optimization of Kalianget Tourism Park and increasing cooperation with investors.